Ethnic variations in sexual behaviours and sexual health markers: findings from the third British National Survey of Sexual Attitudes and Lifestyles (Natsal-3). (October 2017) - Wayal, Sonali; Hughes, Gwenda; Sonnenberg, Pam; Mohammed, Hamish; Copas, Andrew J; Gerressu, Makeda; Tanton, Clare; Furegato, Martina; Mercer, Catherine H
Summary: Background: Sexual health entails the absence of disease and the ability to lead a pleasurable and safe sex life. In Britain, ethnic inequalities in diagnoses of sexually transmitted infections (STI) persist; however, the reasons for these inequalities, and ethnic variations in other markers of sexual health, remain poorly understood. We investigated ethnic differences in hypothesised explanatory factors such as socioeconomic factors, substance use, depression, and sexual behaviours, and whether they explained ethnic variations in sexual health markers (reported STI diagnoses, attendance at sexual health clinics, use of emergency contraception, and sexual function). Methods: We analysed probability survey data from Britain's third National Survey of Sexual Attitudes and Lifestyles (Natsal-3; n=15 162, conducted in 2010–12). Reflecting Britain's current ethnic composition, we included in our analysis participants who identified in 2011 as belonging to one of the following seven largest ethnic groups: white British, black Caribbean, black African, Indian, Pakistani, white other, and mixed ethnicity. We calculated age-standardised estimates and age-adjusted odds ratios for all explanatory factors and sexual health markers for all these ethnic groups with white British as the reference category. We used multivariable regression to examine the extent to which adjusting for explanatory factors explained ethnic variations in sexual health markers. Findings: We included 14 563 (96·0%) of the 15 162 participants surveyed in Natsal-3. Greater proportions of black Caribbean, black African, and Pakistani people lived in deprived areas than those of other ethnic groups (36·9–55·3% vs 16·4–29·4%). Recreational drug use was highest among white other and mixed ethnicity groups (25·6–27·7% in men and 10·3–12·9% in women in the white other and mixed ethnicity groups vs 4·1–15·6% in men and 1·0–11·2% in women of other ethnicities). Compared with white British men, the proportions of black Caribbean and black African men reporting being sexually competent at sexual debut were lower (32·9% for black Caribbean and 21·9% for black African vs 47·4% for white British) and the number of partners in the past 5 years was greater (median 2 [IQR 1–4] for black Caribbean and 2 [1–5] for black African vs 1 [1–2] for white British), and although black Caribbean and black African men reported greater proportions of concurrent partnerships (26·5% for black Caribbean and 38·9% for black African vs 14·8% for white British), these differences were not significant after adjusting for age. Compared with white British women, the proportions of black African and mixed ethnicity women reporting being sexually competent were lower (18·0% for black African and 35·3% for mixed ethnicity vs 47·9% for white British), and mixed ethnicity women reported larger numbers of partners in the past 5 years (median 1 [IQR 1–4] vs 1 [1–2]) and greater concurrency (14·3% vs 8·0%). Reporting STI diagnoses was higher in black Caribbean men (8·7%) and mixed ethnicity women (6·7%) than white British participants (3·6% in men and 3·2% in women). Use of emergency contraception was most commonly reported among black Caribbean women (30·7%). Low sexual function was most common among women of white other ethnicity (30·1%). Adjustment for explanatory factors only partly explained inequalities among some ethnic groups relative to white British ethnicity but did not eliminate ethnic differences in these markers. Interpretation: Ethnic inequalities in sexual health markers exist, and they were not fully explained by differences in their broader determinants. Holistic interventions addressing modifiable risk factors and targeting ethnic groups at risk of poor sexual health are needed. Funding: Medical Research Council, the Wellcome Trust, the Economic and Social Research Council, UK Department of Health, and The National Institute for Health Research.